Law Enforcement Against the Criminal Acts of Murder in Jurisdiction Metro Jaya Regional Police - Bagus Pambudi, Idham; Suwondo, Denny (UNISSULA Semarang, 2025)
The purpose of this research is to find out and analyze; 1) implementation of law enforcement against the crime of mugging in the jurisdiction of the Metro Jaya Regional Police; and 2) formulation of formal law enforcement against the crime of mugging in the jurisdiction of the Metro Jaya Regional Police. The approach method used is sociological juridical, meaning that the method or procedure used by the author is to go directly to the field to obtain updated primary data related to the research topic, namely data regarding law enforcement efforts against the crime of mugging in the jurisdiction of the Metro Jaya Regional Police. Sociological juridical research is conducted by examining the law in reality in society. The results of the study show that: 1) The police as law enforcers are obliged to be responsible for criminal acts committed by members of the mugging group in order to prevent and overcome criminal acts that occur in the jurisdiction they are responsible for through law enforcement. The efforts made by Polda Metro Jaya in enforcing the law on the crime of mugging in the jurisdiction of Polda Metro Jaya are through 2 (two) approaches, namely through preventive efforts and repressive efforts which result in legal sanctions or create a deterrent effect for groups of muggers who have committed crimes; 2) The formulation of law enforcement against the crime of mugging in the jurisdiction of Polda Metro Jaya involves preventive and repressive measures. Preventive efforts include; 1) increasing security by conducting routine patrols, raids, and special operations in areas prone to mugging, especially at night; 2) Counseling and socialization by providing counseling to the community about the dangers of mugging and how to avoid it, as well as increasing legal awareness; 3) Cooperation with the community by forming a voluntary security team, such as FKPM, Pokdar Kamtibmas, and involving community leaders, youth, and religious leaders in prevention efforts, and 4) Supervision and early detection by increasing supervision in areas prone to robbery and conducting early detection of potential criminal acts. Repressive efforts include: 1) Investigation and inquiry by conducting a quick and thorough investigation and inquiry into cases of robbery that occur, by collecting strong evidence; 2) Arrest, namely arresting the perpetrators of robbery based on sufficient evidence; 3) Prosecution, namely prosecuting the perpetrators in court in accordance with applicable legal provisions, and 4) Imposing sanctions, namely giving sanctions appropriate to the perpetrator's actions, including imprisonment and fines.